Analisis Nilai Karakter dalam Kegiatan Bermain Peran Anak Usia Dini - Dina Amalia; Dwi Prasetiyawati Diyah Hariyanti (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2022)
Character education is now indeed a major issue of education, apart from being part of the process of forming the nation's children's character, character education is also expected to be the main foundation in the success of Indonesia Gold 2025. Seeing these problems we need a method that can be used to improve the character of discipline, creativity, hard work and communication skills in class. One method that can be used is role playing. Role playing activities in kindergarten can achieve optimal achievement of all aspects of child development. The purpose of this study is to describe the character values ​​that appear during the role play. This research is a qualitative research based on the philosophy of postpositivism. The results of the research show that there are several character values ​​that are integrated in role playing, namely religious values, discipline values, honest values, hard work values, creative values, independent values, curiosity values, national spirit values, friendly/communicative values, love values. peace, the value of reading, the value of caring for the environment, the value of social care, the value of democracy, and the value of responsibility. The impact of character value analysis research in role playing is the integration of several character values ​​in role playing activities.